Reinserción social un derecho fundamental en el sistema penitenciario, casos Centro Penitenciario de Sahuayo, Michoacán, en el periodo agosto 2019 – agosto 2025 - Alquicira Vázquez, Yaksi Kinari (Universidad Michoacana de San Nicolas de Hidalgo, 2025)
This research, conducted to obtain the Master’s degree in Law, aims to analyze issues related to social reintegration, with the purpose of highlighting the urgent need to design and implement public policies directed toward achieving the reintegration of individuals who are or have been subjected to a penal measure or sanction consisting of deprivation of liberty. To that end, and in addition to addressing key concepts necessary for understanding this subject—such as criminal procedure, criminology, criminogenesis, penology, prevention, public policy, post-penitentiary services, and penal populism—a historical review is carried out on the use and purpose of prison institutions from the precolonial period to the present day. In light of the above, it is pertinent to delve into the study of the current regulatory framework governing social reintegration in Mexico, at the international, national, and local levels—the latter focusing on the State of Michoacán de Ocampo, where the Sahuayo Penitentiary Center is located. From this institution, an exploration of its current situation is undertaken, including two case studies of individuals legally deprived of their liberty, in order to emphasize the proposal for a biphasic and ambivalent model of social reintegration.

La presente investigación para obtener el grado de Maestría en Derecho tiene por objeto realizar el análisis de los temas concernientes a la reinserción social, a fin de mostrar imperiosa necesidad de crear políticas públicas encaminadas a lograr la reinserción social de las personas que se sujetan o sujetaron a una medida o sanción penal consistente en prisión privativa de la libertad. Para ello, además de abordar conceptos importantes en el entendimiento de esta, tales como proceso penal, criminología, criminogenésis, penología, prevención, políticas públicas, servicios postpenitenciarios y populismo penal, se realiza un recorrido histórico sobre el uso o destino brindado desde la época precolonial hasta la fecha a las instituciones penitenciarias. Para lo anterior, es pertinente adentrarse en el estudio del marco normativo vigente de la reinserción social en México, ello en los ámbitos internacional, nacional y local, este último enfocado al Estado de Michoacán de Ocampo, lugar donde ubica el Centro Penitenciario de Sahuayo, del cual se materializa una exploración sobre la situación actual de este y dos estudios de caso de personas legalmente privadas de la libertad ahí recluidas, para de este modo acentuar la propuesta de una reinserción social bifásica y ambivalente.
Facultad de Derecho y Ciencias Sociales. Maestría en Derecho
Keywords: info:eu-repo/classification/cti/5; FDCS-M-2025-1718; Procesal constitucional; Reinserción social; Políticas públicas; Proceso penal; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/19512